Beyond the consult: Outcomes following pediatric VAD referral - Shannon Oliver, MBBS; Asseel Alsalmi, MD; Tara Pidborochynski, MSc; Holger Buchholz, MD; Simon Urschel, MD; Paula Holinski, MD; Vijay Anand, MD; Diana Ly, RN; Jennifer Conway, MD (JHLT Open)
Background: Little is known about patients who are referred for ventricular assist device (VAD) therapy but not implanted. The purpose of this study is to describe their outcomes at 1-year post initial consultation. Methods: Retrospective analysis for patients referred to our VAD services between 01/2019 and 12/2023. Outcomes were reported at 30 days and 1-year post-consult. Patients who died, were too unwell for VAD or required extracorporeal membrane oxygenation (ECMO) within 30 days of consultation were considered acute referrals. Multivariate logistic regression analysis was used to determine risk factors for being an acute referral. Results: There were 128 patients included, with median age at referral 2.7 years (IQR 0.3, 0.9), 50.8% being male, and 52.3% of patients having congenital heart disease (CHD). The primary indication for VAD consult was due to the patient undergoing a transplant evaluation. At 30 days 31% (n = 41) were considered acute referrals, with 28.1% (n = 36) receiving ECMO, 3.1% (n = 4) being too unwell for VAD, and 0.8% (n = 1) patients dying. Patients who were acute referrals and had not received VAD therapy or transplant had worse 1-year survival (p < 0.001) then elective referrals, with the highest risk for mortality being early in the course. Diagnosis of biventricular CHD, other (non-CHD, non-cardiomyopathy) or absence of co-morbidities were independent factors associated with being an acute referral. Conclusion: Of patients referred to the VAD service, one-third were considered acute referrals. Patients who were acute referrals had increased 1-year mortality than those who were elective referrals. Factors associated with being an acute referral included diagnosis of biventricular CHD or other and no co-morbidities.